2010
DOI: 10.1017/s0022109010000785
|View full text |Cite
|
Sign up to set email alerts
|

Information Shocks, Liquidity Shocks, Jumps, and Price Discovery: Evidence from the U.S. Treasury Market

Abstract: In this paper, we identify jumps in U.S. Treasury-bond (T-bond) prices and investigate what causes such unexpected large price changes. In particular, we examine the relative importance of macroeconomic news announcements versus variation in market liquidity in explaining the observed jumps in the U.S. Treasury market. We show that while jumps occur mostly at prescheduled macroeconomic announcement times, announcement surprises have limited power in explaining bond price jumps. Our analysis further shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
112
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(124 citation statements)
references
References 45 publications
8
112
1
3
Order By: Relevance
“…Moreover, authors show that liquidity shocks play a key role in explaining jumps and that usually, during the preannouncement period, it is possible to observe a drop in market depth. [3] explain this result as that, as also discussed in [4], dealers tend to withdraw orders and place them further out to avoid 35 being picked off in the upcoming information event. Thus, authors conclude that jumps observed in correspondence to macroannouncement releases are not only determined by news, but also by the drop in liquidity that is a market mover per se.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Moreover, authors show that liquidity shocks play a key role in explaining jumps and that usually, during the preannouncement period, it is possible to observe a drop in market depth. [3] explain this result as that, as also discussed in [4], dealers tend to withdraw orders and place them further out to avoid 35 being picked off in the upcoming information event. Thus, authors conclude that jumps observed in correspondence to macroannouncement releases are not only determined by news, but also by the drop in liquidity that is a market mover per se.…”
mentioning
confidence: 58%
“…[2] point out the advantage of using very high frequency data to study the impact of such events. On the other hand, [3] conclude 30 that although a majority of jumps occurs at prescheduled news announcement times, surprises related to macroannouncements have limited power in explaining bond price jumps. Moreover, authors show that liquidity shocks play a key role in explaining jumps and that usually, during the preannouncement period, it is possible to observe a drop in market depth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al identify jumps in U.S. Treasury-bond prices and investigate what causes such unexpected large price changes. They find that preannouncement liquidity shocks have significant predictive power for jumps, which occur mostly at prescheduled macroeconomic announcement times, announcement surprises have limited power in explaining bond price jumps [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…W centrum zainteresowania niniejszego opracowania są skoki, czyli gwałtowne zmiany cen mają-ce znaczenie z punktu widzenia pomiaru ryzyka, zarządzania nim, alokacji aktywów w portfelach, jak również wyceny instrumentów pochodnych (Jiang, Lo i Verdelhan, 2011). Celem niniejszego artykułu jest zbadanie zachowania się miar płynności w okresach występowania skoków cenowych.…”
Section: Wprowadzenieunclassified